Convenient Access to Carbohydrate–BODIPY Hybrids by Two Complementary Methods Involving One‐Pot Assembly of "Clickable" BODIPY Dyes. Issue 26 (23rd July 2014) - Martinez‐Gonzalez, Mayra R.; Urías‐Benavides, Arlette; Alvarado‐Martínez, Enrique; Lopez, J. Cristobal; Gómez, Ana M.; del Rio, Mayca; Garcia, Inmaculada; Costela, Angel; Bañuelos, Jorge; Arbeloa, Teresa; Lopez Arbeloa, Iñigo; Peña‐Cabrera, Eduardo
Abstract: Two complementary one‐pot, three component synthetic strategies based on copper(I)‐catalyzed azide–alkyne cycloadditions (CuAAC) have been developed, which allow the efficient assembly of glycosyl‐derived alkynes or azides with highly fluorescent boron–dipyrromethene (BODIPY) cores containing azido or alkyne moieties, respectively. The resulting carbohydrate–BODIPY derivatives display excellent photophysical and laser properties that relate to the spacer (amino group or aromatic ring) employed in each of the synthetic protocols. Abstract : Two complementary one‐pot, three‐component methodologies are described that allow the click copper(I)‐catalyzed azide–alkyne cycloaddition of azido– or alkyne–carbohydrates with alkyne– or azide–BODIPY derivatives, respectively, and pave the way to water‐soluble carbohydrate–difluoroboron‐dipyrromethene hybrids.